LANGUAGE LEARNING FOR YOUNG LEARNERS - Allaberganova Dilnoza (Modern American Journals, 2025)
Language learning in early childhood is a crucial foundation for cognitive, social, and academic development. Young learners possess a unique ability to acquire new sounds, vocabulary, and grammatical structures naturally through exposure and interaction. This paper examines the significance of early language learning, reviews key literature, and discusses methods and strategies suitable for young learners. It also highlights the role of teachers, parents, and technology in supporting language acquisition. The proposed recommendations aim to create engaging, immersive, and age-appropriate learning environments. The study concludes by emphasizing the long-term academic and personal benefits of early language education.